A randomised controlled trial of extended anticoagulation treatment versus standard treatment for the prevention of recurrent venous thromboembolism (VTE) and post‐thrombotic syndrome in patients being treated for a first episode of unprovoked VTE (the ExACT study). (12th November 2019) - Bradbury, Charlotte; Fletcher, Kate; Sun, Yongzhong; Heneghan, Carl; Gardiner, Chris; Roalfe, Andrea; Hardy, Pollyanna; McCahon, Debbie; Heritage, Gail; Shackleford, Helen; Hobbs, FD Richard; Fitzmaurice, David
Summary: Venous thromboembolism (VTE) is prevalent and impactful, with a risk of death, morbidity and recurrence. Post‐thrombotic syndrome (PTS) is a common consequence and associated with impaired quality of life (QoL). The ExACT study was a non‐blinded, prospective, multicentred randomised controlled trial comparing extended versus limited duration anticoagulation following a first unprovoked VTE (proximal deep vein thrombosis or pulmonary embolism). Adults were eligible if they had completed ≥3 months anticoagulation (remaining anticoagulated). The primary outcome was time to first recurrent VTE from randomisation. The secondary outcomes included PTS severity, bleeding, QoL and D‐dimers. Two‐hundred and eighty‐one patients were recruited, randomised and followed up for 24 months (mean age 63, male:female 2:1). There was a significant reduction in recurrent VTE for patients receiving extended anticoagulation [2·75 vs. 13·54 events/100 patient years, adjusted hazard ratio (aHR) 0·20 (95% confidence interval (CI): 0·09 to 0·46, P < 0·001)] with a non‐significant increase in major bleeding [3·54 vs. 1·18 events/100 patient years, aHR 2·99 (95% CI: 0·81–11·05, P = 0·10)]. Outcomes of PTS and QoL were no different between groups. D‐dimer results (on anticoagulation) did not predict VTE recurrence. In conclusion, extended anticoagulation reduced VTE recurrence but did not reduce PTS or improve QoL and was associated with a non‐significant increase in bleeding. Results also suggest very limited clinical utility of D‐dimer testing on anticoagulated patients.